Clinical and biochemical characterization of the prothrombin Belgrade mutation in a large Serbian pedigree: new insights into the antithrombin resistance mechanism. (24th February 2017) - Miljic, P.; Gvozdenov, M.; Takagi, Y.; Takagi, A.; Pruner, I.; Dragojevic, M.; Tomic, B.; Bodrozic, J.; Kojima, T.; Radojkovic, D.; Djordjevic, V.
Abstract : Essentials Prothrombin Belgrade mutation leads to antithrombin resistance. Clinical and biochemical phenotypes in a large family with this mutation were investigated. In carriers, we detected decreased factor II activity and increased endogenous thrombin potential. Prothrombin Belgrade mutation represents a strong prothrombotic risk factor. Summary: Background: The recently reported c.1787G>A mutation in the prothrombin gene leads to Arg596Gln replacement in the protein molecule (prothrombin Belgrade). This substitution impairs binding of antithrombin to thrombin and results in inherited thrombophilia, known as antithrombin resistance. Objectives: We aimed to elucidate the clinical and biochemical characteristics of thrombophilia associated with antithrombin resistance in a large Serbian family with the prothrombin Belgrade mutation. Patients and methods: Nineteen family members were investigated, among whom 10 were carriers of the c.1787G>A mutation. In all subjects the clinical phenotype was determined and laboratory investigations of hemostatic parameters were performed. Results: Six out of the 10 mutation carriers developed thromboembolic events, mainly deep venous and mesenteric vein thrombosis. The median age of the first thrombotic event was 26.5 (12–41) years, whereas the incidence rate of first thrombosis was 2.2% per year. In all mutation carriers prothrombin activity was significantly decreased in comparison with non‐carriers, clearly distinguishing each group. However, the presence of the mutation did not affect the prothrombin antigen level in plasma. The endogenous thrombin potential was significantly increased in all carriers in comparison with non‐carriers, indicating the presence of blood hypercoagulability. Interestingly, levels of D‐dimer and the F1+2 fragment were similar in both groups. Conclusions: Although rare, the prothrombin Belgrade mutation represents strong thrombophilia with early onset of thrombosis in the investigated family. According to our results, decreased prothrombin activity may be a simple screening test for detection of this mutation in thrombotic patients.